EMOTIONALLY-VALUABLE COMPONENT OF INFORMATION COMPETENCE OF POLICEMAN - Karpushina, Natalia (PSYCHOLOGICAL JOURNAL, 2017)
The article is devoted to finding out of question about ponderability of emotionally-valued component of informative competence of investigator in the process of investigation of crymes. Modern looks are outlined to the role of emotionally-volitional and valued-incentive sphere of personality of investigator in providing of effective investigation. In particular, it is set in researches, that the features of these spheres in investigation activity are predetermined by system co-operation of normatively-legal, socialpsychological and activity-operational factors. In the article the results of comparative research of emotionally-valued determinants of informative competence are represented for the informatively experienced and non-experienced investigators. A presence is well-proven enough expressive personality adaptation potential for the experienced investigators, which characterize the high level of orientation in the situations of co-operation, satisfy emotional firmness and capacity for the rapid making of strategies of behavior. To the same category of inspected inherent insignificant risk of destructive influence of negative emotions on intercourse which determines actual absence of emotional problems in informative communication. Ponderability of some values is set in research, what inherent to the valued-orientation sphere personalities of investigators with experience 5 over. It terminal values are «vital wisdom», «health», «public confession» and instrumental is «rationalism», «self-control» and «hard will». The noted differences can be used in the system of professional selection on positions of investigation Ministry of Internal Affairs of Ukraine and organization of professional studies.